Carcinocythemia: A rare entity becoming more common? A 3‐year, single institution series of seven cases and literature review. (14th September 2018) - Ronen, Shira; Kroft, Steven H.; Olteanu, Horatiu; Hosking, Paul R.; Harrington, Alexandra M.
Abstract: Introduction: Carcinocythemia is a rare phenomenon defined as morphologically identifiable, circulating tumor cells in the peripheral blood. No modern case series of carcinocythemia exists in the literature. Methods: Blood smears from carcinocythemia patients were reviewed and associated clinicopathologic findings described and compared to the literature. When available, bone marrows were examined. Results: We identified 7 carcinocythemia cases over 3 years at our institution in 5 females and 2 males with a median age of 57 and compare them to 26 case reports in the literature (19 females, 10 males; median age 57). The primary neoplasms were carcinomas of breast (3 cases), lung, non‐small cell (2 cases), prostate (1), and 1 case of unknown primary. Circulating tumor cells were associated with fragmentation hemolysis (2 cases), asplenic RBC changes (3 cases), and myeloid antigen expression by flow cytometry (2 cases) and were most commonly found at the feathered edge of the slide (6 cases) as single cells or in clusters. Conclusions: This represents the largest series of carcinocythemia reported. The identification of 7 cases at one institution over a 3‐year period suggests carcinocythemia may becoming more common. Raising awareness of this entity and its associated clinicopathologic findings may help avoid diagnostic pitfalls in blood smear examinations and may guide timely clinical management.